Cysteine–based redox regulation and signaling in plants - Couturier, Jérémy; Chibani, Kamel; Jacquot, Jean-Pierre; Rouhier, Nicolas (Frontiers in Plant Science, 2013)
Living organisms are subjected to oxidative stress conditions which are characterized by the production of reactive oxygen (ROS), nitrogen (RNS) and sulfur (RSS) species. In plants as in other organisms, many of these compounds have a dual function as they damage different types of macromolecules but they also likely fulfil an important role as secondary messengers. Owing to the reactivity of their thiol groups, some protein cysteine residues are particularly prone to oxidation by these molecules. In the past years, besides their recognized catalytic and regulatory functions, the modification of cysteine thiol group was increasingly viewed as either protective or redox signalling mechanisms. The most physiologically relevant reversible redox post-translational modifications (PTMs) are disulfide bonds, sulfenic acids, S-glutathionylated adducts, S-nitrosothiols and to a lesser extent S-sulfenylamides, thiosulfinates and S-persulfides. These redox PTMs are mostly controlled by two oxidoreductase families, thioredoxins and glutaredoxins. This review focuses on recent advances highlighting the variety and physiological roles of these PTMs and the proteomic strategies used for their detection.